Welcome to our community

Be a part of something great, join today!

Linear transformation

Petrus

Well-known member
Feb 21, 2013
739
Hello MHB,
given a linear transformation F so that this is known
\(\displaystyle \left\{
\begin{aligned}
\phantom{1}F(1,0,0)=(1,2,3) \\
F(1,1,0)=(0,0,1)\\
F(1,1,1)=(12,3,4)\\
\end{aligned}
\right.\)
Decide F

progress:
\(\displaystyle F(e_1)=(1,2,3)\)
\(\displaystyle F(e_2)=F(e_1)+F(e_2)-F(e_1)=(0,0,1)-(1,2,3)=(-1,-2,-2)\)
\(\displaystyle F(e_3)=F(e_1)+F(e_2)+F(e_3)-(F(e_1)+F(e_2))= (12,3,4)-(-1,-2,-2)=(13,5,6)\)
My \(\displaystyle f(e_3)\) is wrong acording to facit and I don't understand

Regards,
\(\displaystyle |\pi\rangle\)
 

Petrus

Well-known member
Feb 21, 2013
739
Hello MHB,
I have seen what my misstake was... I forgot that \(\displaystyle F(e_2)=(-1,-2,-2)\) that means \(\displaystyle F(e_1)+F(e_2)=(0,0,1)\) so \(\displaystyle F(e_3)=(12,3,3)\) I was not thinking clear, I did confuse this in my brain but now I see!

Regards,
\(\displaystyle |\pi\rangle\)